Mathematical input-output analysis for economic impact assessment: A case study on local government's bridge construction project - Suresh Kumar Sahani; Binod Kumar Sah; Kameshwar Sahani; Rahul Das; Ashok Kumar Mahato (Fakultas Tarbiyah Universitas Ibrahimy, 2024)
This paper explores the application of Input-Output Analysis (IOA) in evaluating the economic impacts of infrastructure projects, emphasizing its mathematical foundations. Using a hypothetical case study, the paper demonstrates how IOA, as a mathematics-based analytical tool, can help local governments assess the broader economic implications of building a new bridge. By incorporating direct effects, such as construction costs and job creation, and induced effects, such as local worker spending, the analysis reveals the total economic impact of the project. The method of research uses secondary data, such as government reports, regional economic indicators, and previous infrastructure evaluations, to estimate changes in employment, income, and value-added output. The findings highlight how IOA can provide valuable insights for policymakers to make informed decisions about public investments that stimulate local economies.